2012
DOI: 10.4304/tpls.2.9.1939-1944
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Self-regulated Learning Components and L2 Vocabulary Knowledge and Reading Comprehension

Abstract: Abstract-In the past two decades, self-regulation has been the center of heated debate in educational psychology. The present study attempted to investigate the relationship between Iranian EFL learners' selfregulated learning components and vocabulary knowledge and reading comprehension .To fulfill this objective, a 60-item vocabulary and reading comprehension TOEFL test was administered to a sample of 250 male and female college students majoring in English Teaching, English Language Translation, and English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
4
13
0
3
Order By: Relevance
“…As Alexander and Jeton (2000) state, students who are taught strategies start to think metacognitively about strategies to improve their reading. Findings of the present study resonate with several other studies, e.g., Ghaith and Amal (2003); Jacob, Rottenberg, Patrick, and Wheeler (1996); Khezrlou (2012); Shokrzade (2010);and Zarei (2012). Shokrzade (2010) studied the impact of metacognitive strategies and critical thinking ability on learner comprehension and found that metacognitive strategy instruction had a positive impact on learners' reading comprehension.…”
Section: Kruskal-wallis Test Bsupporting
confidence: 89%
See 1 more Smart Citation
“…As Alexander and Jeton (2000) state, students who are taught strategies start to think metacognitively about strategies to improve their reading. Findings of the present study resonate with several other studies, e.g., Ghaith and Amal (2003); Jacob, Rottenberg, Patrick, and Wheeler (1996); Khezrlou (2012); Shokrzade (2010);and Zarei (2012). Shokrzade (2010) studied the impact of metacognitive strategies and critical thinking ability on learner comprehension and found that metacognitive strategy instruction had a positive impact on learners' reading comprehension.…”
Section: Kruskal-wallis Test Bsupporting
confidence: 89%
“…Both increased their positive attitude and finally caused them to like reading more. Zarei (2012) investigated the effect of cooperative activities on Iranian learners' reading comprehension, and his study did not confirm a superior effect of cooperative learning over non-cooperative learning with respect to reading comprehension among advanced general English proficiency level students. He found that low proficiency level students gained more from communicative activities than the more advanced students.…”
Section: Pedagogical Implicationsmentioning
confidence: 96%
“…Similarly, Ayatollahi, Rasekh, and Tavakoli's (2012) findings were likely to confirm the idea that part of the achievements in L2 academic reading ability can be the result of SRLSs and epistemological beliefs. Furthermore, Zarei and Hatami's (2012) research suggested that the relationships between self-regulated learning (SRL) components and reading comprehension knowledge of learners are mixed. Moreover, Al Asmari and Mahmoud Ismail (2012) found that some of the SRLSs are predictors of reading comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…Un grupo de estudiantes en formación docente aún no han vivido una experiencia significativa al interior de las asignaturas. Por esto, es necesario orientar la lectura de los textos académicos en función epistémica para que los estudiantes puedan tener contacto con la producción académica disciplinar y darle un sentido significativo a la lectura (Zarei y Hatami, 2012), y así hacer "uso del lenguaje para pensar, descubrir, transformar, crear y construir el saber" (Serrano Moreno, 2014).…”
Section: Evaluación De Las Necesidades Frente a Las Prácticas De Lecturaunclassified